Operations Research - D S Hira; Prem Kumar Gupta (New Delhi, 2023)
Comprehensively written in a manner that suites the students of Mechanical Engineering and Commerce & Management, "Operations Research" transmutes deftly into a resource or a reference text for the students of statistics and mathematics or aspirants of various entrance examinations including UPSC.Coverage of popular topics such as Linear Programming, Probability Theory and Queuing Models are supplemented with numerous examples, tables and figures which are then followed by exercises thereby providing the assurance to fulfil every requirement of understanding of the student. A book which has seen, foreseen and incorporated changes in the subject for more than 40 years, it continues to be one of the most sought-after texts by the students.
English
Keywords: Management; Operations Management